Trace gas exchange by subarctic vegetation under global climate change - Seco, Roger; Holst, Thomas; Davie-Martin, Cleo L.; Rieksta, Jolanta; Smart, Amy; Rinnan, Riikka (Asociación Española de Ecología Terrestre, 2023)
Peer reviewed